PENGGUNAAN FERMENTASI EKSTRAK RAMUAN HERBALTERHADAP INCOME OVER FEED COST (IOFC) DAN NILAI EKONOMIS PAKAN PADA PEMELIHARAAN AYAM BROILER - Dyah, Dyah (FAPETKAN UNTAD, 2014)
The aimed of this research was to evaluate the effect of using fermented extracted herbals on income over feed cost (IOFC) and feed economic effiency on broiler rearing. Material used were80 unsexing DOC strain MB-202 produced by PT. Japfa Comfeed Indonesia Tbk. Herbals used includegarlic (Allium sativum L.), ginger (Zingiber officinale Rosc. var. rubrum), turmeric (Zingiber officinale Rosc.), wild ginger (Curcuma xanthorrhiza ROXB), and betel leaf (Piper Betle L.). Herbals were extracted, mixed,and fermented with EM4. then added to drinking water. The experiment usedaComplete Randomized Design with 4 treatments and 4 replications. The treatments were 0%, 10%, 15%, and 20% fermented extracted herbals in drinking water. The basal feedwas commercial complete feed produced by PT. Charoen Pokphand Indonesia. Results showed that there were no significant effect (P>0.05) on using fermented extractedherbals to income over feed cost (IOFC) and feed economic efficiency on broiler rearing. Income over feed costÂ (Rp/chicken) were 5,099,75 ; 4,758,92 ; 4,530,34 ; and 4,053,26 respectively. Feed economic efficiency (Rp/chicken) were 12,061,09 ; 12,244,09 ; 12,094,16, and 12,500,86 respectively. It could be concluded that using fermented extracted herbals did not influence income over feed cost (IOFC) and feed economic efficiency on broiler rearing. Keywords: Fermented extracted herbals, income over feed cost, feed economic efficiency, broiler.